2017
DOI: 10.4103/1008-682x.192033
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of MAGEG2 with testis-specific expression in mice

Abstract: Male germ cell development is a well-defined process occurring in numerous seminiferous tubules of the testis. Uncovering testicular novel genes related to intrinsic regulation of spermatogenesis is essential for the understanding of spermatogenesis. In the present study, we investigated mouse Mageg2, which belongs to a group of melanoma-associated antigens (MAGEs). Mageg2 is transcribed in the testis specifically, and its expression level is increased at the pachytene spermatocyte stage, indicating that Mageg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 48 publications
1
1
0
Order By: Relevance
“…Consistently, a previous study reported that the loss of EXOSC10 in spermatogonia could lead to abnormal testicular development and a strongly decreased size (Jamin et al, 2017). HSPA9 has also shown low methylation levels at the promoter and is expressed at a high level in the testis, which plays an important role in prophase I of spermatogenesis by binding to testis-specific MAGEG2 (Melanoma Antigen Family G2) (Jeong et al, 2017). These results show that these conserved HMRs between the testis and sperm could be important candidate regions for the study of spermatogenesis and male infertility.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Consistently, a previous study reported that the loss of EXOSC10 in spermatogonia could lead to abnormal testicular development and a strongly decreased size (Jamin et al, 2017). HSPA9 has also shown low methylation levels at the promoter and is expressed at a high level in the testis, which plays an important role in prophase I of spermatogenesis by binding to testis-specific MAGEG2 (Melanoma Antigen Family G2) (Jeong et al, 2017). These results show that these conserved HMRs between the testis and sperm could be important candidate regions for the study of spermatogenesis and male infertility.…”
Section: Discussionsupporting
confidence: 74%
“…Several genes with hypomethylated promoter regions were highly expressed in the testis (Figure 4B). In particular, EXOSC10 (exosome component 10) and HSPA9 (heat shock protein family member 9) have been suggested to play important roles in male germ cell development (Jamin et al, 2017;Jeong et al, 2017).…”
Section: Comparison Of Hmrs Between Porcine Sperm and Testismentioning
confidence: 99%